Community participation in developing and applying criteria and indicators of sustainable and equitable forest management - Burford de Oliveira, N. (Center for International Forestry Research, 1999)
Between March 1997 and February 1998 three tests of Criteria and Indicators (C&I) for assessing the sustainability of community-managed forests were conducted by the Center for International Forestry Research. The tests, each lasting approximately one month, were sited in humid forest in Central Province, Cameroon; Sanggau, West Kalimantan, Indonesia; and in the Arapiuns river basin, Para, Brazil. Each test was carried out by an interdisciplinary team composed of a social scientist or anthropologist, an ecologist and a forest management specialist, in consultation with the local community. This paper discusses some of the concepts and methodologies used in the tests. An overview is provided of the main results of community participation in the processes of developing and testing C&I. Two themes given prominence by the testing teams were participation in, and knowledge of, forest management and its social dimensions. Focus is on these interlinked themes, discussing how participatory processes of developing and applying C&I can be expanded to identify and realise learning potential on all sides. The popular and partnership educational/learning curricula are described as suitable mechanisms for introducing participatory C&I development processes. The document concludes by describing a range of research and extension activities suitable for participatory C&I development that can form part of the educational curricula discussed.